EFFECT OF CENTELLA ASIATICA L. ON THE NUMBER OF OSTEOCLASTS, OSTEOBLASTS, AND OSTEOCYTES IN THE TIBIAE OF OVARIECTOMIZED RATS - KARIS, VANISSA; SOEKANTO, SRI ANGKY; IDRUS, ERIK (International Journal of Applied Pharmaceutics, 2019)
Objective: This study aimed to examine the effectiveness of Centella asiatica L. as a phytoestrogen. Methods: Therapy using C. asiatica extract at doses of 60 mg/kg body weight, 120 mg/kg BW, and 180 mg/kg BW was administered to ovariectomized rats for 30 days. Results: Histological examination using hematoxylin and eosin staining demonstrated an increased number of osteocytes and a decreased number of osteoclasts, but there was no significant increase in osteoblast numbers. Conclusion: The administration of the low doses of C. asiatica extract affects the number of osteocytes and osteoclasts but not osteoblasts in ovariectomized rats.